Effect of Moisture Content on some Physical Properties of Red Kidney Bean (Phaseolus vulgaris L.) Seed Grown in North Eastern Nigeria - Aviara , N. A.; Ma’aji, R. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
This study was aimed at determining some physical properties of red kidney bean seed as a function of moisture content. In the moisture range of 6.84-15.74% (d.b), seed length, width and thickness increased from 11.4-16.83mm, 6.2-8.87mm and 4.3-5.16mm, and Arithmetic and Geometric diameters increased from 8.6-10.29mm and from 8.3-9.14mm, respectively. In the above moisture range, one thousand seed weight, seed surface area, true density, and porosity increased linearly, while sphericity increased logarithmically, and angle of repose increased as a polynomial of the second order with moisture content. Bulk density decreased with increase in moisture content in the above moisture range. Static coefficient of friction on all the structural surfaces applied increased logarithmically with moisture content, and kinetic coefficient of friction on the surface all increased linearly with moisture content except on fiber glass where the increase was polynomial of the second order. Static and kinetic coefficients of friction were highest on Hessian bag material and lowest on fiber glass. Regression models that could be used to express the relationship between the physical properties and moisture content, with high coefficients of determination, were established. The data obtained in this study would be applicable in the design of red kidney bean seed handling and storage facilities.